C-C Bond Formation through Reductive Coupling of CS 2 to Yield Uranium Tetrathiooxalate and Ethylenetetrathiolate Complexes - Lam, Oanh P.; Heinemann, Frank Wilhelm; Meyer, Karsten (Angewandte Chemie International Edition, 2011)
A novel twist: The U complex [(( ArO) N)U] reacts with CS by reductive coupling to form the tetrathiooxalate complex [(( ArO) N)U (- : -C S )] with a newly formed C-C bond (see scheme). The U /U tetrathiooxalate complex features a nonplanar C S unit in an unprecedented - : binding mode. Further reduction gives the ethylenetetrathiolate complex [Na(dme) ] [(( ArO) N)U (-C S )]. DME=1,2-dimethoxyethane. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.